Antimicrobial activity and molecular docking screening of bioactive components of Antirrhinum majus (snapdragon) aerial parts. Issue 8 (August 2022) - Saqallah, Fadi G.; Hamed, Wafaa M.; Talib, Wamidh H.; Dianita, Roza; Wahab, Habibah A.
Abstract: Background: Antirrhinum majus (Snapdragon) is a perennial Mediterranean-native plant that is commonly used for mass display. Few reports acknowledged the traditional use of A. majus for its medicinal and therapeutic effects. Herein, we assess the impact of A. majus 's sample preparation and extraction methods on the plant-aerial parts' phytochemical contents and antimicrobial activity. Furthermore, the microbial targets of the extracts' secondary metabolites are inspected using molecular docking simulations. Methods: The leaves and flowers of A. majus were prepared as fresh and air-dried samples, then extracted using cold maceration and hot reflux, respectively. Extracts with the best phytochemical profiles were selected to test their antimicrobial activities against Bacillus subtilis, Staphylococcus aureus, Enterobacter aerogenes, Escherichia coli and Candida albicans . Besides, molecular docking of 66 reported isolated compounds was conducted against various microbial targets. Results: The dried-refluxed samples revealed a massive deterioration in their phytochemical profiles, whereas the macerated flowers extract exhibited the highest total phenolic content and antimicrobial activity against all tested bacterial strains. However, both flowers and leaves extracts showed similar minimum inhibitory and lethal concentrations against C. albicans . Molecular docking studies revealed that chlorogenic acid, chalcononaringenin 4'-glucoside, 3, 4, 2', 4', 6'-pentahydroxy-chalcone 4'-glucoside, apigenin-7-glucuronide, and luteolin-7-glucuronide were the lead compounds in expressing the antimicrobial activity. Yet, A. majus 's compounds could neither inhibit the 30S ribosomal subunit nor muramyl ligase E. Conclusion: Our results suggest that cold maceration of A. majus fresh aerial parts gave higher flavonoid and phenolic content contributing to its antimicrobial properties. These flavonoids and phenolic compounds are predicted to have a crucial role in inhibiting fungal sterol 14-demethylase, and bacterial dihydropteroate synthase and gyrase B subunit proteins. Graphical abstract: Image 1 Highlights: Air-drying of A. majus 's aerial parts deteriorates its phytochemical composition, affecting its antimicrobial activity. A. majus 's fresh-flowers macerate exhibited the highest total phenolic content and antibacterial activity. The antimycotic activity of A. majus was the same for flowers and leaves macerates. In-silico results showed that some phenolics, chalcones, and flavonoids are responsible for the antimicrobial activity. A. majus 's components act on fungal sterol 14-demethylase, and bacterial dihydropteroate synthase and gyrase B enzymes. Abstract : Antirrhinum majus ; Reflux extraction; Maceration extraction; Total phenolic content; Antimicrobial activity; Molecular docking.